Prospects for the diagnosis and gene therapy of inherited retinal dystrophies caused by biallelic mutations in the RPE65 gene - V. V. Neroev; L. A. Katargina; V. V. Kadyshev; I. V. Zolnikova; S. I. Kutsev (Российский офтальмологический журнал, 2021)
Inherited retinal dystrophies (IRD) is an extensive group of genetically heterogeneous diseases with significant clinical polymorphism. With the development of gene therapy, a new era in the treatment of hereditary  human diseases has opened. To date, clinical studies of a number of gene  medications are performed the world over, including those intended for the  treatment of hereditary eye diseases (Leber congenital amaurosis (LCA), retinitis pigmentosa, achromatopsia, Stargardt's disease, choroideremia, etc.). The varieties of two former conditions, specifically LCA type 2 and retinitis pigmentosa (RP) type 20 with biallelic mutations in the RPE65 gene belong to IRD. Epidemiological studies indicate the rarity of these diseases, which explains why IRD caused by biallelic mutations in the RPE65 gene are  included into the list of rare (orphan) diseases of the Russian Ministry of Health. For these IRDs, a gene replacement therapy has been developed:  voretigen neparvovek, which must only be applied once. Currently, the Medical Genetic Research Center and Helmholtz National Medical Research Center of Eye Diseases have identified a group of patients who meet the  criteria for genetic therapy. In 2021, а specialized gene therapy center has been established at the Helmholtz Research Center, which was certified by the Ministry of Health. A group of leading experts in the field of inherited retinal diseases and medical genetics developed and approved at  professional workshops a number of measures that promote the introduction into clinical practice of the voretigen neparvovek as a gene replacement therapy for the treatment of RPE65-related IRD in the Russian Federation.